A capsule-type composite material and its preparation method and application
By using capsule composite materials in solid-state lithium-ion batteries, the shell is cracked by using voltage electric fields and/or heating, and the composite materials are exposed, the problem of material being sensitive to moisture is solved, and the battery production with lower cost and higher stability is achieved.
Patent Information
- Application Number
- CN202510075831.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The materials of existing solid-state lithium-ion batteries are sensitive to moisture in the environment, resulting in high humidity requirements during production and use, limiting their large-scale production and application.
Capsule-type composite materials are used to crack the shell under the action of voltage electric field and/or heating, exposing the wrapped composite materials, thereby avoiding contact with water when used in the battery.
It effectively protects moisture-sensitive materials, reduces the requirements of production process for environmental humidity, simplifies the preparation process, reduces costs, and improves the consistency and stability of the product.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a capsule-type composite material and a preparation method and application thereof. Background Art
[0002] Traditional lithium-ion batteries use liquid electrolytes, such as lithium iron phosphate batteries and ternary material batteries commonly used in electric vehicles. This type of battery is called a liquid battery; the liquid electrolyte has a low ignition point and is prone to fire and explosion. At the same time, the energy density of liquid lithium-ion batteries has reached its ceiling; therefore, it is imperative to develop safer and higher energy density batteries.
[0003] Solid-state batteries have the advantages of high safety and high energy density, and are the future direction of battery development. However, the problem faced by existing solid-state batteries is that the materials used, such as electrolytes and lithium metals, are sensitive to moisture in the environment, which makes them have high requirements for environmental humidity during the use process. This leads to the inability to popularize solid-state battery technology and limits mass production. In view of this, the present invention provides a capsule-type composite material and its preparation method and application. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a capsule-type composite material and a preparation method and application thereof, with the aim of providing a solid-state battery with low manufacturing cost, mass production, high product consistency and stability.
[0005] The technical solution of the present invention to solve the above technical problems is as follows: In a first aspect, a capsule-type composite material is provided, wherein the capsule-type composite material mainly consists of a shell layer and a composite material wrapped in the shell layer; the shell layer breaks down under the action of a voltage electric field and / or heating, exposing the composite material wrapped in the shell layer.
[0006] The beneficial effect of the present invention is that the present invention coats and protects the materials that are sensitive to moisture used in existing solid-state batteries, so that they are wrapped in a waterproof shell during transportation and battery preparation and are not in contact with water in the outside air. This can not only protect the materials that are sensitive to moisture, but also reduce the requirements for the process environment. Therefore, the preparation process of the solid-state batteries produced is simple, can be mass-produced and used, and reduces manufacturing costs and improves product consistency and stability.
[0007] Based on the above technical solution, the present invention can also be improved as follows.
[0008] Furthermore, the maximum diameter of the capsule-type composite material is 0.01 μm to 20 μm; And / or, the mass ratio of the shell layer to the composite material is 0.55-5:95-99.45; And / or, the material of the shell layer includes a high molecular polymer; And / or, the composite material includes an electrolyte.
[0009] The beneficial effect of adopting the above further solution is that when the diameter of the composite material is less than 0.01 μm, the processing performance will be poor, and when the diameter is greater than 20 μm, it is not conducive to the performance.
[0010] Furthermore, the electrolyte includes at least one of sulfide, halide, oxide, and electrolyte polymer; the electrolyte accounts for 0-100% of the weight of the composite material.
[0011] And / or, the high molecular polymer includes at least one of polyethylene (PE), polypropylene (PP), polyamide (PA), and fluorine-containing high molecular polymers.
[0012] The beneficial effect of adopting the above further solution is that the moisture-sensitive material can be coated to prevent contact with water.
[0013] Furthermore, the composite material also includes at least one of a conductive agent, an active material, a binder, and an additive.
[0014] Furthermore, the conductive agent includes at least one of carbon and olefin; the conductive agent accounts for 0% to 10% of the weight of the composite material; And / or, the binder includes at least one of fluorine-containing, acrylic, and polyimide; the binder accounts for 0-100% of the weight of the composite material; And / or, the active material includes any one of a positive electrode sensitive active material and a negative electrode sensitive active material; the active material accounts for 0-100% of the weight of the composite material; And / or, the additive includes at least one of VC (vinylene carbonate), LiPF6, and lithium powder; the additive accounts for less than 1% of the weight of the composite material.
[0015] Furthermore, when the shell layer breaks down under the action of voltage electric field and / or heating, the voltage used is 100V~1000V, and the duration is less than 10s; and / or the heating used is at 80℃~200℃, and the duration is 12h~96h.
[0016] The beneficial effect of adopting the above further scheme is that the composite material is exposed, which not only protects the composite material from being sensitive to moisture, but also allows the composite material to be evenly dispersed in the electrode / diaphragm to facilitate performance.
[0017] In a second aspect, a method for preparing a capsule-type composite material comprises the following steps: The material of the shell layer is made into a film of required thickness; the composite material is stirred evenly under the environment of -40°C at the leak point to obtain a mixed composite material; The mixed composite material is completely coated with the film by a pressing method at a leak point of -40°C and a pressing temperature of 120°C to 200°C to obtain a capsule-type composite material.
[0018] The beneficial effect of adopting the above solution is that materials that are sensitive to moisture can be coated to prevent contact with water.
[0019] A third aspect provides a solid-state lithium battery, comprising the capsule-type composite material.
[0020] The beneficial effect of adopting the above scheme is that the solid-state battery using the capsule-type composite material has a simple preparation process and reduces production costs.
[0021] In a fourth aspect, a method for preparing a solid-state lithium battery comprises the following steps: Preparation of a positive electrode doped or coated with the capsule-type composite material; and / or preparation of a negative electrode doped or coated with the capsule-type composite material; and / or preparation of a diaphragm coated with the capsule-type composite material; The solid-state lithium battery is assembled and packaged according to the assembly process of the battery cell, and then the capsule-type composite material is cracked under the conditions of a voltage of 100V-1000V and a duration of less than 10s, and / or a heating temperature of 80°C-200°C and a time of 12h-96h, so that the composite material wrapped in the capsule-type composite material is exposed to obtain a solid-state lithium battery.
[0022] The beneficial effect of adopting the above scheme is that the composite material is exposed in a confined space, which not only protects the composite material from being sensitive to moisture, but also allows the composite material to be evenly dispersed in the electrode / diaphragm to facilitate performance.
[0023] Furthermore, when preparing a positive electrode doped with the capsule-type composite material, the capsule-type composite material accounts for 0-99% of the weight of the positive electrode material; And / or, when preparing a positive electrode coated with the capsule-type composite material, the thickness of the coating layer of the positive electrode containing the capsule-type composite material is 10 μm-500 μm; and / or, when preparing a negative electrode doped with the capsule-type composite material, the capsule-type composite material accounts for 0-99% by weight of the negative electrode material; And / or, when preparing a negative electrode coated with the capsule-type composite material, the thickness of the coating layer of the negative electrode containing the capsule-type composite material is 10 μm-500 μm; And / or, when preparing a separator coated with the capsule-type composite material, the thickness of the coating layer containing the capsule-type composite material is 3 μm-50 μm.
[0024] The beneficial effect of adopting the above further solution is that the capsule-type material can be used on the positive electrode, the negative electrode and the separator respectively. DETAILED DESCRIPTION
[0025] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased through regular channels.
[0026] The present embodiment relates to a capsule-type composite material, which is mainly composed of a shell layer and a composite material wrapped in the shell layer; the shell layer breaks under the action of a voltage electric field and / or heating, exposing the composite material wrapped in the shell layer.
[0027] Preferably, in this embodiment, the maximum diameter of the capsule-type composite material is 0.01μm~20μm, specifically 0.01μm, 0.1μm, 1μm, 5μm, 10μm, 15μm, 20μm, etc. A diameter less than 0.01μm is not conducive to dispersion, and particles larger than 20μm affect the ion transmission rate; the capsule-type composite material can be in various shapes, including but not limited to spherical, cylindrical, and various irregular shapes.
[0028] And / or, the mass ratio of the shell layer to the composite material is 0.55~5:95~99.45, specifically 0.55:99.45, 5:95, etc.; and / or, the material of the shell layer includes a polymer, wherein the polymer has the function of isolating water, has a certain elasticity, and can withstand a pressure greater than 1 MPa; and / or, the composite material includes an electrolyte; specifically, the composite material can be liquid, solid, or granular.
[0029] In this embodiment, the polymer includes at least one of polyethylene (PE), polypropylene (PP), polyamide (PA), and fluorine-containing polymers; wherein the fluorine-containing polymer includes PTFE, PFA, and PVDF; And / or, the electrolyte includes at least one of sulfide, halide, oxide, and electrolytic polymer; the electrolyte accounts for 0-100% of the weight of the composite material, specifically 3%, 10%, 20%, 60%, 90%, etc. The sulfide includes one or a combination of LPSCl, LGPS, and LISICON; the halide includes Li a -M-Cl6、Li a -M-Cl4 and Li a -M-Cl8 or a combination thereof; the oxide comprises a garnet (LLZO) structure, a perovskite (LLTO) structure, or a NASICON sodium superion conductor type; the polymer comprises a PEO-based, PAN-based, PMMA-based, and PVDF-based electrolyte or a combination thereof.
[0030] In this embodiment, preferably, the composite material further includes at least one of a conductive agent, a binder, an active material, and an additive.
[0031] In this embodiment, the conductive agent includes at least one of carbon and olefin, wherein the carbon includes graphite, conductive carbon black, Ketjen black, carbon nanotubes, carbon nanofibers, etc.; the olefin includes graphene, etc.; the conductive agent accounts for 0.1% to 10% of the weight of the composite material, specifically 0.1%, 1%, 5%, 10%, etc.; And / or, the binder includes at least one of fluorine-containing, acrylic, and polyimide, and / or, the active material includes any one of positive electrode sensitive active materials and negative electrode sensitive active materials, such as lithium metal and its compounds, sulfur and its compounds, or materials sensitive to solvents such as nano-silicon materials, etc.; the active material accounts for 0-100% of the weight of the composite material, specifically 3%, 10%, 20%, 60%, 90%, etc.; And / or, the additive includes at least one of lithium salts, lithium supplements, carbonates, and silanes, and the additive is beneficial to improving the SEI film or adjusting the interfacial tension; the additive accounts for less than 1% of the weight of the composite material, specifically 1%, 0.5%, 0.1%, etc.
[0032] In this embodiment, when the shell layer is cracked under the action of voltage electric field and / or heating, the voltage used is 100V~1000V, specifically 100V, 200V, 500V, 800V, etc., and the duration is less than 10s, specifically 1s, 3s, 5s, 8s, etc.; and / or the heating used is 80℃~200℃, specifically 80℃, 100℃, 150℃, 200℃, etc., and the duration is 12h~96h, specifically 12h, 24h, 48h, 60h, 72h, 96h, etc. Under this condition, the composite material wrapped in the shell layer is exposed, and the exposed composite material can be filled in the nearby pores to play the role of transmitting ions / electrons / storing ions.
[0033] This embodiment also relates to a method for preparing a capsule-type composite material, which is prepared by using a method for preparing soft capsules in the pharmaceutical industry, and includes the following steps: making a shell material into a film of a required thickness; stirring the composite material evenly at a leak point of -40°C to obtain a mixed composite material; A pressing method is adopted under a leak point environment of -40°C, and the pressing temperature adopted is 120°C to 200°C, specifically 120°C, 160°C, 180°C, 200°C, etc. The mixed composite material is completely coated with the film to obtain a capsule-type composite material.
[0034] This embodiment also relates to a solid-state lithium battery, which includes the capsule-type composite material.
[0035] The present embodiment also relates to a method for preparing a solid-state lithium battery, comprising the following steps: preparing a positive electrode doped or coated with the capsule-type composite material; and / or preparing a negative electrode doped or coated with the capsule-type composite material; and / or preparing a diaphragm coated with the capsule-type composite material; specifically: adding the capsule-type composite material to the positive electrode material by a dry process or a wet process, and / or adding it to the negative electrode material, and / or coating it on the surface of the diaphragm, and / or coating it on the surface of the positive electrode, and / or coating it on the surface of the negative electrode; The solid-state lithium battery is assembled and packaged according to the assembly process of the battery cell, and the voltage used is 100V~1000V, specifically 100V, 200V, 500V, 800V, etc., and the duration is less than 10s, specifically 1s, 3s, 5s, 8s, etc.; and / or the heating used is 80℃~200℃, specifically 80℃, 100℃, 150℃, 200℃, etc., and the time is 12h~96h, specifically 12h, 24h, 48h, 60h, 72h, 96h, etc. Under this condition, the capsule-type composite material is cracked, and the composite material wrapped in the capsule-type composite material is exposed to obtain a solid-state lithium battery. It can play a functional role in the subsequent capacity and aging test process.
[0036] Preferably, in this embodiment, when preparing a positive electrode doped with the capsule-type composite material, the capsule-type composite material accounts for 0-99% of the weight of the positive electrode material, specifically 0%, 10%, 20%, 60%, 90%, etc.; And / or, when preparing a positive electrode coated with the capsule-type composite material, the thickness of the coating layer of the capsule-type composite material is 10 μm-500 μm, specifically 10 μm, 50 μm, 100 μm, 200 μm, 300 μm, 400 μm, 500 μm, etc.; And / or, when preparing a negative electrode doped with the capsule-type composite material, the capsule-type composite material accounts for 0-99% by weight of the negative electrode material, specifically 0%, 10%, 20%, 60%, 90%, etc.; And / or, when preparing a negative electrode coated with the capsule-type composite material, the thickness of the coating layer of the capsule-type composite material is 10 μm-500 μm, specifically 10 μm, 50 μm, 100 μm, 200 μm, 300 μm, 400 μm, 500 μm, etc.; And / or, when preparing a diaphragm coated with the capsule-type composite material, the thickness of the coating layer containing the capsule-type composite material is 3μm-500μm, specifically 3μm, 10μm, 50μm, 100μm, 200μm, 300μm, 400μm, 500μm, etc.
[0037] It can be seen that this embodiment coats and protects the moisture-sensitive materials used in existing solid-state batteries, so that they are wrapped in a waterproof shell during transportation and battery preparation, and do not come into contact with water in the outside air. This can protect the moisture-sensitive materials and reduce the requirements for the process environment. Therefore, the solid-state battery preparation process is simple, can be mass-produced and used, and reduces manufacturing costs and improves product consistency and stability. The following uses specific embodiments for further explanation.
[0038] Embodiment 1: This embodiment relates to a method for preparing a conventional solid-state lithium battery, comprising the following steps: (1) Preparation of positive electrode sheet, negative electrode sheet and diaphragm coated with LPSC (Li6PS5Cl): The positive electrode uses the traditional NCM electrode P1, and the negative electrode material uses the traditional graphite electrode N1, where N1 / P1=1.1 meets the lithium-ion battery design standards.
[0039] The diaphragm uses a 6μm PE substrate diaphragm, and a 2μm thick sulfide LPSC coating is coated on the A and B surfaces of the diaphragm. Since LPSC is relatively insensitive to moisture in the environment, it reacts immediately when in contact with moisture and releases hydrogen sulfide toxic gas. In order to prevent LPSC from contacting water, it is necessary to prepare LPSC slurry and coating in a glove box / drying room with a leak point below -40°C. The specific steps are as follows: Preparation of LPSC slurry: In a glove box / drying room with a leak point below -40°C, LPSC and binder ethylene acrylate copolymer (EMA) are dissolved in toluene solvent. After the LPSC slurry is fully dispersed, it is coated on a 6μm PE substrate diaphragm. The toluene solvent is then dried by baking and the toluene needs to be collected to prevent environmental hazards. The single-sided thickness of the coating after drying is 4μm±0.5μm, and the thickness of the 6μm PE base film diaphragm after coating is 14±1μm, obtaining an LPSC coating on the substrate diaphragm. This coating is called LPSC-1#.
[0040] (2) Cell assembly: Since the LPSC coating is still very active and cannot come into contact with water, the cell assembly is still carried out in a glove box / drying room, and the leak point still needs to be below -40°C. The positive electrode, LPSC coating separator, and negative electrode are assembled according to the assembly process of 18650 batteries. After baking, sealing, formation, and aging, the distribution of formation capacity, internal resistance, and k value are obtained, and the cell performance is tested.
[0041] Embodiment 2: This embodiment relates to a method for preparing a solid-state lithium battery, comprising the following steps: (1) The same positive electrode sheet, negative electrode sheet and 6 μm PE base film as in Example 1 were used, except for the preparation of LPSC capsule particles, LPSC slurry and LPSC coating. The specific preparation steps for the preparation of LPSC capsule particles, LPSC slurry and LPSC coating are as follows: Preparation of LPSC capsule particles: First, heat and dissolve the PE (polyethylene) masterbatch at room temperature and humidity to prepare a film with a thickness of 0.5±0.2μm. Under a leak point of less than -40°C, the LPSC particles are prepared using the preparation method of soft capsules in the pharmaceutical industry. The LPSC powder is completely wrapped with a PE film to prepare elliptical particles with a maximum diameter of 2±0.5μm. The outer shell of this particle is a waterproof PE film. Even when immersed in water, it can isolate water from entering. The LPSC capsule particles can be placed and used at room temperature and humidity.
[0042] Preparation of LPSC coating: At room temperature and humidity, LPSC capsule particles are mixed evenly with aqueous PVDF glue commonly used in lithium batteries, and then coated on a 6μm PE base film using a ceramic diaphragm coating process and baked. The single-sided thickness of the coating after drying is 4μm±0.5μm, and the thickness of the 6μm PE base film diaphragm after coating is 14±1μm. This coating is called LPSC-2#.
[0043] (3) Cell assembly: This is carried out in a lithium-ion battery workshop with normal temperature and humidity control. The general temperature is 25±5°C and the humidity is <30RH%. The positive electrode, LPSC-2# separator and negative electrode are assembled according to the assembly process of 18650 batteries. After baking and sealing, the capsule is broken at 80°C with a high voltage of 200V / 2s. Then, the formation and aging processes are carried out to obtain the distribution of formation capacity, internal resistance and k value and test the cell performance.
[0044] Test example: (1) Distribution of capacity, internal resistance, k value and test cell performance.
[0045] The tests of capacity, internal resistance, K value and electrical performance are carried out in accordance with the lithium battery industry standards.
[0046] (2) Product consistency and stability testing: the standard requires PpK>1.67.
[0047] The distribution of capacity, internal resistance, k value and the results of the test cell performance test are shown in Table 1.
[0048] Table 1 Data of Example 1 and Example 2 It can be seen from Table 1 that the expected distribution of the mean data of the batch cells made by Example 2 of the invention is not lower than the mean and distribution of the batch cells made by Example 1 between strict leakage points, and the rate and cycle life data are not lower than those of Example 1.
[0049] From the comparison between Examples 1 and 2, it can be seen that Example 1 needs to be carried out in a drying room with a strict leak point below -40°C, and protection is required from the LPSC slurry to the sealing process. This environment requires high energy consumption, and once there is a control error and the humidity increases, hydrogen sulfide will be released, poisoning incidents will occur, and the consistency of the battery performance cannot be guaranteed, and it is impossible to mass-produce safely and stably; in Example 2, by pre-coating the LPSC and isolating it from contact with water, not only the safety guarantee of the LPSC is improved, but also the environmental requirements are greatly reduced, that is, it can be implemented in the environment of a conventional lithium-ion battery preparation factory and mass production; therefore, the present invention provides a guarantee for lithium-ion solid-state batteries to be more low-cost, higher energy density, safer production, and easy to mass-produce.
[0050] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A capsule-type composite material, characterized in that: The capsule-type composite material mainly consists of a shell layer and a composite material wrapped in the shell layer. The shell layer is cracked under the action of a voltage electric field and / or heating, exposing the composite material wrapped in the shell layer.
2. A capsule-type composite material according to claim 1, characterized in that: The maximum diameter of the capsule-type composite material is 0.01 μm to 20 μm; And / or, the mass ratio of the shell layer to the composite material is 0.55-5:95-99.45; And / or, the material of the shell layer includes a high molecular polymer; And / or, the composite material includes an electrolyte.
3. A capsule-type composite material according to claim 2, characterized in that: The electrolyte includes at least one of sulfide, halide, oxide, and electrolyte polymer; the electrolyte accounts for 0-100% of the weight of the composite material; And / or, the high molecular polymer includes at least one of polyethylene, polypropylene, polyamide, and fluorine-containing high molecular polymers.
4. The capsule-type composite material according to claim 2, characterized in that: The composite material further comprises at least one of a conductive agent, an active material, a binder and an additive.
5. A capsule-type composite material according to claim 4, characterized in that: The conductive agent includes at least one of carbon and olefin; the conductive agent accounts for 0% to 10% of the weight of the composite material; And / or, the binder includes at least one of fluorine-containing, acrylic, and polyimide; the binder accounts for 0-100% of the weight of the composite material; And / or, the active material includes any one of a positive electrode sensitive active material and a negative electrode sensitive active material; the active material accounts for 0-100% of the weight of the composite material; And / or, the additive includes at least one of VC, LiPF6, and lithium powder; the additive accounts for less than 1% of the weight of the composite material.
6. The capsule-type composite material according to any one of claims 1 to 5, characterized in that: When the shell layer breaks down under the action of voltage electric field and / or heating, the voltage used is 100V~1000V, and the duration is less than 10s; and / or the heating used is at 80℃~200℃, and the duration is 12h~96h.
7. A method for preparing a capsule-type composite material according to any one of claims 1 to 6, characterized in that: The steps include: The material of the shell layer is made into a film; the composite material is stirred evenly at a leak point of -40°C to obtain a mixed composite material; The mixed composite material is completely coated with the film by a pressing method at a leak point of -40°C and a pressing temperature of 120°C to 200°C to obtain a capsule-type composite material.
8. A solid-state lithium battery, characterized in that: The solid-state lithium battery comprises a capsule-type composite material as described in any one of claims 1 to 6.
9. A method for preparing a solid-state lithium battery according to claim 8, characterized in that: The steps include: Preparation of a positive electrode doped or coated with the capsule-type composite material according to any one of claims 1 to 6; and / or preparation of a negative electrode doped or coated with the capsule-type composite material according to any one of claims 1 to 6; and / or preparation of a separator coated with the capsule-type composite material according to any one of claims 1 to 6; The solid-state lithium battery is assembled and packaged according to the assembly process of the battery cell, and then the capsule-type composite material is cracked under the conditions of a voltage of 100V-1000V and a duration of less than 10s, and / or a heating temperature of 80°C-200°C and a time of 12h-96h, so that the composite material wrapped in the capsule-type composite material is exposed to obtain a solid-state lithium battery.
10. The method for preparing a solid-state lithium battery according to claim 9, characterized in that: When preparing a positive electrode doped with the capsule-type composite material, the capsule-type composite material accounts for 0-99% of the weight of the positive electrode material; And / or, when preparing a positive electrode coated with the capsule-type composite material, the coating layer of the capsule-type composite material has a thickness of 10 μm-500 μm; and / or, when preparing a negative electrode doped with the capsule-type composite material, the capsule-type composite material accounts for 0-99% by weight of the negative electrode material; And / or, when preparing a negative electrode coated with the capsule-type composite material, the coating layer of the capsule-type composite material has a thickness of 10 μm-500 μm; And / or, when preparing a separator coated with the capsule-type composite material, the thickness of the coating layer containing the capsule-type composite material is 3 μm-50 μm.